Promosi Kesehatan Gizi di Lingkungan Sekolah - Sariana, Sariana; Azahra, Putri; Adzan, Muh Nur Zaky; Fajar, Nur Fadillah Putri; Riyadi, Laode Ahmad (akultas Ilmu Sosial dan Ilmu Politik, 2025)
Nutritional health promotion in schools is a strategic effort to form healthy living behaviors from an early age. This article discusses the importance of nutrition education, the role of schools as agents of change, and effective strategies in implementing nutritional health promotion. The methods used are literature studies and field observations in several secondary schools. The results of the study indicate that the integration of nutrition education in the curriculum, the involvement of healthy canteens, and routine nutrition campaigns contribute positively to increasing students' awareness and behavior towards consuming healthy foods. This study recommends strengthening healthy school policies and teacher training to support the sustainability of school nutrition programs. Keywords: Nutrition; Health Promotion; Nutrition Education ABSTRAK Promosi kesehatan gizi di sekolah merupakan upaya strategis untuk membentuk perilaku hidup sehat sejak dini. Artikel ini membahas pentingnya edukasi gizi, peran sekolah sebagai agen perubahan, serta strategi efektif dalam penerapan promosi kesehatan gizi. Metode yang digunakan adalah studi literatur dan observasi lapangan di beberapa sekolah menengah. Hasil penelitian menunjukkan bahwa integrasi edukasi gizi dalam kurikulum, keterlibatan kantin sehat, serta kampanye gizi rutin berkontribusi positif terhadap peningkatan kesadaran dan perilaku siswa terhadap konsumsi makanan sehat. Penelitian ini merekomendasikan penguatan kebijakan sekolah sehat dan pelatihan guru untuk mendukung keberlanjutan program gizi sekolah. Kata Kunci: Gizi; Promosi Kesehatan; Edukasi Gizi